Yalıtımlı Bir Kabinde Farklı Akışkanlar İçin Bağıl Nemin Sıcaklığa Göre Değişimin Deneysel Olarak İncelenmesi - Koyun, Tansel; Avcı, Semih (Fırat University, 2015)
Ortamların iklimlendirilmesinde konfor şartları büyük önem taşır. Bir ortam iklimlendirmesinde iklimlendirme cihazının yaz, kış ya da her ikisinin olması durumuna göre ısıtma, soğutma, nemlendirme, nem alma ve taze hava verme gibi işlemler söz konusu olur. Konfor şartlarını belirleyen en önemli etkenler olarak sıcaklık ve bağıl nem sayılabilir. Bu durum göz önüne alınarak bu çalışmada havanın, ısıtılan farklı akışkanların buharıyla nemlendirilmesi için bir kabin hazırlanmıştır. Kabin içerisindeki ortam havasının dışarıdan ısı alışverişiyle etkilenmemesi için kabin yalıtılmıştır. Kabin içindeki havanın sirkülasyonu sağlanması amacıyla 2 tane pc fanı kullanılmıştır. Her bir akışkan için, 5 farklı sıcaklıkta nem ölçüm deneyleri yapılmıştır. Bu ölçümler yapılırken ölçme cihazı olarak kabin içerisinde sıcaklık ve nem sensörleri kullanılmıştır. Burada amaç farklı akışkanların havayı nemlendirme kabiliyetlerini analiz etmek olmuştur. Elde edilen sonuçlar grafikler halinde sunulmuştur. Deneyde kullanılan her üç akışkan için de doyma basınçları ile çiğ noktası sıcaklıkları arasındaki değişimin doğru orantılı olduğu görülmüştür. Ayrıca doyma basıncına göre çiğ noktası sıcaklıklarının değişiminin tuzlu su için diğer iki akışkana göre daha yüksek değerlere sahip olduğu da görülmüştür.

Acclimatised to the conditions of comfort in the environment is of great importance. of air conditioning equipment in an environment in summer, winter or air conditioning is not fully based on the condition of heating, cooling, humidification, dehumidification and fresh air would be like making processes concerned. Terms of comfort as the most important factors include temperature and relative humidity. In this study considering this state of the air, which is heated with steam for moistening a container of different fluids were prepared. Heat exchange with the ambient air in the container from the outside of the container is insulated to avoid exposure. In order to ensure circulation of the air inside the container two of the computer fan units were used. For each fluid, tests humidity measurement were carried out at five different temperatures. These measurements were made as measuring devices have been used within the container temperature and humidity sensors. In this study, air humidification abiltiy different liquid aim. The results obtained were graphed. it was seen as a direct proportion between the change of the saturation pressure of the dew point temperature for three fluids used in the experiment.Also change of the dew point temperature according to the saturation pressure, It is also seen to have higher values than the other two fluid for salty water.
Experimental Investigation of Relative Humidity depend on the temperature for Different Fluids in a Insulation container